2014
DOI: 10.1371/journal.pone.0087094
|View full text |Cite
|
Sign up to set email alerts
|

Straw Mulching Reduces the Harmful Effects of Extreme Hydrological and Temperature Conditions in Citrus Orchards

Abstract: Extreme weather conditions with negative impacts can strongly affect agricultural production. In the Danjiangkou reservoir area, citrus yields were greatly influenced by cold weather conditions and drought stress in 2011. Soil straw mulching (SM) practices have a major effect on soil water and thermal regimes. A two-year field experiment was conducted to evaluate whether the SM practices can help achieve favorable citrus fruit yields. Results showed that the annual total runoff was significantly (P<0.05) reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 35 publications
8
28
1
Order By: Relevance
“…According to Walczak and Usowicz (1994), crop residue retention impacts soil thermal regimes due to the ability to reflect soil radiation, reduce evaporation and influence net heat exchange, temperature gradient and heat transfer. Liu et al (2014) reported that, because straw mulch covering soil surface has higher albedo and lower thermal conductivity than the bare soil, it reduces the solar radiation reaching the soil and consequently reduces the soil temperature.…”
Section: Effect Of Tillage and Mulching On Soil Bulk Density Temperamentioning
confidence: 99%
“…According to Walczak and Usowicz (1994), crop residue retention impacts soil thermal regimes due to the ability to reflect soil radiation, reduce evaporation and influence net heat exchange, temperature gradient and heat transfer. Liu et al (2014) reported that, because straw mulch covering soil surface has higher albedo and lower thermal conductivity than the bare soil, it reduces the solar radiation reaching the soil and consequently reduces the soil temperature.…”
Section: Effect Of Tillage and Mulching On Soil Bulk Density Temperamentioning
confidence: 99%
“…Straw mulch has been shown to prevent soil evaporation in relay-planting systems when the earlier-planted component crop is harvested (Wang et al 2004). Furthermore, straw mulching has been shown to decrease the depth of crop rooting in some cases, leading to reduced root interaction and competition between the two relay-planted crops during their cogrowth period (Liu et al 2014). …”
Section: Soil Water Movement and Competitionmentioning
confidence: 99%
“…An increase in soil temperature under bicolour mulches may be attributed to the fact that these mulches absorb more radiation from sun and transmit more heat to the upper layer of soil as compared to organic mulches. Various workers Kathiravan, 2009 andLiu et al, 2014) also found an increase in soil temperature with polythene and straw mulches. Walsh et al, (1996) found higher soil temperature under cultivation as compared to straw mulch in apple.…”
Section: Soil Temperaturementioning
confidence: 93%